Recognition versus self-determination : dilemmas of emancipatory politics - Eisenberg, Avigail; Webber, Jeremy H. A., 1958-; Coulthard, Glen, 1974- (Ethnicity and democratic governance series., 2014)
The political concept of recognition has introduced new ways of thinking about the relationship between minorities and justice in plural societies. But is a politics informed by recognition valuable to minorities today? Contributors to this volume examine the successes and failures of struggles for recognition and self-determination in relation to claims of religious groups, cultural minorities, and indigenous peoples on territories associated with Canada, the United States, Europe, Latin America, India, New Zealand, and Australia. The cases look at cultural recognition in the context of public policy about both intellectual and physical property, membership practices, and independence movements, while probing debates about toleration, democratic citizenship, and colonialism. Together the contributions point to a distinctive set of challenges posed by a politics of recognition and self-determination to peoples seeking emancipation from unjust relations.